Формування та ревіталізація середмість історичних міст України - Рибчинський, Олег Валерійович (Національний університет "Львівська політехніка", 2017)
Мета дослідження - визначити етапи історико-архітектурного формування, виявити актуальні проблеми та розробити стратегії ревіталізації середмість історичних міст України. У дисертації середмістя розглядається як першоджерело формування історичного міста України, цілісний архітектурно-містобудівний комплекс та однин із основних місцевих ресурсів перспективного розвитку поселення. В результаті аналізу та систематизації визначено основні історико-архітектурні етапи формування та уточнено закономірності розпланування середмість; архітектурно-просторову типологію, особливості функціонального, конструктивного та стилістичного вирішення забудови у XVI – на початку ХХ ст. Уточнено основні етапи занепаду середмість у ХХ ст. та виявлено сім актуальних станів їхньої функціонально-просторової збереженості. В роботі обґрунтовано цінність, визначено актуальні проблеми збереження, ресурси функціонально-просторового розвитку та опрацьовано програмну модель комплексної ревіталізації середмістя, як парадигми нової якості центру історичного міста. Визначено, що соціальний фактор суттєво впливає на розвиток середмістя. Згідно поставлених завдань сформовано стратегії, послідовність реалізації та індикатори ревіталізації середмість історичних міст України, із врахуванням семи станів їхнього збереження. Цель исследования определить этапы историко-архитектурного формирования, выявить актуальные проблемы и разработать стратегии ревитализации ядра исторических городов Украины. В диссертации ядро рассматривается как первоисточник формирования исторического города Украины, целостный архитектурно-градостроительный комплекс и один из основных местных ресурсов перспективного развития поселения. В результате анализа и систематизации определены основные историко-архитектурные этапы формирования и уточнены закономерности планировки ядра; архитектурно-пространственную типологию, особенности функционального, конструктивного и стилистического решения застройки в XVI - начала ХХ в. Уточнены основные этапы упадка ядра исторического города в ХХ веке и выявлены семь актуальных состояний их функционально-пространственной сохранности. В работе обосновано ценность, определены актуальные проблемы сохранения, ресурсы функционально-пространственного развития и проработано програмную модель комплексной ревитализации ядра как парадигмы нового качества центра исторического города. Определено, что социальный фактор существенно влияет на развитие ядра исторического города. Согласно поставленных задач сформированы стратегии, последовательность реализации и индикаторы ревитализации ядра исторических городов Украины, с учетом степени их сохранения. The aim of the study – to define the stages of historical and architectural formation, to detect the actual problems and to develop a models of strategy for downtown revitalizing of the historic cities of Ukraine. In the thesis the downtown is considered as an origin of a historical Ukrainian town, a holistic architectural and urban complex and one of the main local resources for the development of settlements. The thesis defines five main historical and architectural development stages of a downtown during XVI - early twentieth century. The downtown planning was modernized and regulated under the influence of political and administrative factors. Therefore its designed was changed to a regular or a combined one (with elements of the old planning being preserved). At the end of XVIII - early XX century new quarters and sacred objects were built on the site of the fortifications perimeter. Unique downtown of historic towns in the Left-Bank and Right-Bank of Ukraine, located in the Russian Empire, were fundamentally changed in the first half of the nineteenth century. Significant evolutionary changes occurred in the towns during the XVI - XIX centuries. They became more prudent and sequential. They inherited outer and inner space-planning structure of the downtowns. Though the analysis and systematization, an architectural and spatial typology was defined, along with the specifics of functional, structural and stylistic approaches to buildings in the XVI - early XX century. Main stages of the downtown decays in the twentieth century are clarified. Seven actual conditions of their functional and spatial preservation are defined. The thesis provides substantial arguments towards the value of the downtowns. It identifies the actual problems of their preservation, along with resources of their functional and spatial development. It elaborates on the programming model of the integral revitalization of the downtown as a paradigm of the new quality center of a historical town. It consists of empirical, theoretical, and practical design stage. In projects is solved regeneration problems of entire downtown or market square, restoration of monuments, rehabilitation of important buildings and residential sector, qualitative development of economy and culture, the formation of a new quality protection and preservation of the cultural heritage by the local community, development of public associations, animations of seats memory, town identity and traditions.The thesis states that social factor significantly effects the development of a downtown. According to the objectives of the research, strategies for the revitalization of the historic Ukrainian downtowns are introduced taking into account the seven states of their preservation. Seven general indicators of the revitalization quality are defined. Quantitative indicators of revitalization are defined by: sources and increased investments; restoration and adaptation of architectural monuments; patronage; intensification of socio-economic life in the market square; improvements of territories around the ancient town fortifications; international cooperation and success of youth policy; formation of recreation areas. Developed a new concept of downtown development as the primary source the historic town formation of Ukraine and one of the main local resource of perspective development of settlement. Formulate scientific recommendations for the protection, preservation and revitalization of the downtown area. Implementation the results of work will facilitate the development of research on the theory and restoration of architectural monuments and urban planning, improve and increase the level of project activity, provide the effectiveness of processing and implementing programs of strategic development of the historical town.
Формирование и ревитализация ядра исторических городов Украины
The formation and revitalization of the downtown historic towns of Ukraine
Keywords: формування; ревіталізація; середмістя; історичне місто; спадщина; розпланування; забудова; збереження; ресурси розвитку; програмна модель; формирование; ревитализация; ядро исторического города; наследие; планировка; застройка; сохранение; ресурсы развития; програмная модель; formation; revitalization; downtown; historic town; heritage; planning; building; preservation; resources development; programming model